SCIENTISTS' IDEAS ABOUT THE ROLE OF NATURE-CONFORMING EDUCATION IN THE FORMATION OF PERSONALITY (American Journal of Pedagogical and Educational Research, 2025)
This article examines the ideas of various scientists of that time about the role of nature-conforming education in the formation of personality.